Acoustics of icelandic lava caves. (August 2022) - Małecki, Paweł; Lipecki, Tomasz; Czopek, Dorota; Piechowicz, Janusz; Wiciak, Jerzy
Highlights: Icelandic lava caves sounds good. Lava caves walls in concert halls. Acoustic analysis of lava caves. Abstract: Lava caves are a broad group of caves formed by various volcanic processes. These unique and spectacular wonders of nature have a very surprising acoustic climate that can be described as very dry and intimate in comparison with the acoustics of typical rock caves. The paper shows the results of over 70 spatial impulse measurements in three different lava tubes located in west and southwest Iceland. The basic room acoustic parameters and Sound Pressure Levels were measured or calculated together with parametric statistical analysis. Moreover, laser scanning of the cave's geometry was conducted. The obtained reverberation time varies from 0.1 to 0.9 s for medium frequencies and up to 2 s for low ones and is similar in all three measured lava tubes. The performed measurements and analyses showed that materials and structures similar to those found in lava tubes could be used as sound absorbing equipment in concert halls or seminar rooms. The obtained spatial impulse responses, geometrical and structural data and the performed calculations can also be used in virtual reality systems or utilized while monitoring morphology, erosion progression and even microbiological activity in future.